UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI INTERAKSI EDUKATIF PADA MATA PELAJARAN SOSIOLOGI - Yunita, Yunita; Rustiyarso, Rustiyarso; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is titled Efforts to increase student learning motivation in educational interactions in sociology subjects in XI IPS 3 class at SMA Santo Fransiskus Asisi Pontianak. The background of this research is the low activity of students due to lack of motivation. This research is a class action research. Data collection is done by field notes, observation sheets and documentation. The results showed that: (1) Planning of learning motivation through educative interaction of sociology subjects in Class XI IPS 3 students at SMA Santo Fransiskus Asisi Pontianak first cycle by looking at the results of the planning observation sheet ie, was at 4.25 with a good category as well as at the second cycle is at a value of 4.36 with a good category. (2) The implementation of learning motivation through educative interactions of sociology subjects in Class XI IPS 3 students at SMA Santo Fransiskus Asisi Pontianak, first cycle by looking at the results of the observation sheet which is in value 4 with good category as well as in second cycle which is at value 4, 4 in the good category. (3) There is an increase in motivation to learn through educational interactions in sociology subjects in Class XI IPS 3 students in SMA Santo Fransiskus Asisi Pontianak by 26% where in the first cycle by 45% the category is quite active while in the second cycle is 71% with the active category.Keywords: Efforts to Improve, Learning Motivation, Educational Interactions, Sociology Subjects